Digital Customer Protection: Mediator between Mobile Money Usage and Financial Inclusion - Elizabeth Fiesta Clara Shinta Budiyono; Sukmawati Sukamulja (Media Ekonomi dan Manajemen, 2023)
The development of technology in the 5.0 era, marked by the increase in internet usage, currently impacts people's habits in accessing financial services, such as mobile money usage. Therefore, it aligns with the government's vision to increase financial inclusion through mobile money usage to reduce poverty. However, Yogyakarta Province is a province with a poverty rate that exceeds the national average, and it is the highest in the Java region. In this regard, digital customer protection needs to be considered because mobile money usage carries a high risk to the security and privacy of user data. Therefore, this study aims to determine the role of digital customer protection in mediating mobile money usage and financial inclusion in productive age communities in Yogyakarta. This study applies the Sobel test by Baron and Kenny and the process method by Hayes. The result of this study shows that digital customer protection significantly mediates mobile money usage towards financial inclusion partially in productive age communities in Yogyakarta Province. With these results, it is expected that all parties should work together to increase mobile money usage to reduce poverty and help the government to achieve the welfare of the community.